STYLISH DEVELOPMENT OF EUROPEAN THEMATIC KOVROTKACHESTVA - L.F. Eĭvas (Academy of Cognitive and Natural Sciences, 2022)
The history o f occurrence and development of weaving of thematic carpets - Gobelin tapestries is examined, stile changes in technics and technologies of weaving, a choice of plots and means of expressiveness are analyzed.